2012
DOI: 10.2136/sssaj2012.0070
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Chilled‐Mirror Hygrometer for Measuring Water Potential in Relatively Dry and Partially Frozen Soils

Abstract: Estimating water potential in a relatively dry soil is fundamentally important, not only for predicting soil water flows in arid areas or during the evaporation process, but also for understanding soil freezing processes. A micro-chilledmirror hygrometer (FINEDEW) that does not require a sampling chamber and has a rapid response time has recently been developed. The sensor head can be inserted into a soil sample. We confirmed that FINEDEW directly and quickly measures soil water potential in the range of less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Exposure of a ground surface to subzero temperatures leads to the formation of a frozen soil layer, in which gas, ice, and liquid water coexist (Dash et al, ). The amount of unfrozen water decreases with temperature, which can cause large negative water pressures (Schofield, ; Hohmann, ; Watanabe et al, ). Because negative pressure induces water flow from unfrozen soils at greater depths, the frozen soil layer tends to have a relatively high water content (Iwata et al, ; Tokumoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of a ground surface to subzero temperatures leads to the formation of a frozen soil layer, in which gas, ice, and liquid water coexist (Dash et al, ). The amount of unfrozen water decreases with temperature, which can cause large negative water pressures (Schofield, ; Hohmann, ; Watanabe et al, ). Because negative pressure induces water flow from unfrozen soils at greater depths, the frozen soil layer tends to have a relatively high water content (Iwata et al, ; Tokumoto et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil water flow during the freezing of disturbed soils has been investigated thoroughly using laboratory experiments (Stähli and Stadler, ; Weigert and Schmidt, ) and numerical simulations (Harlan, ; Hansson et al, ). Although the infiltration of water into thawing soils has received less attention than redistribution of water in freezing soils, relationships between water content of the frozen layer and the timing and rate of infiltration have been investigated with field and laboratory observations (Gray et al, ; Watanabe et al, , ). However, ground is rarely uniform; it contains macropores, such as cracks, roots, and animal holes.…”
Section: Introductionmentioning
confidence: 99%
“…Tensiometers have a limited measurement range from 0 kPa to -80 kPa and require frequent maintenance to refill their water (Hillel 1998). Only in-situ psychrometers measure matric potentials lower than -500 kPa (Watanabe et al 2012); however, their measurements are susceptible to the influence of temperature, and therefore, they cannot be used for subsurface soils experiencing dynamic temperature changes. Give that psychrometers measure the sum of matric potential and osmotic potential, they may overestimate the soil dryness when the soil contains solutes.…”
Section: Introductionmentioning
confidence: 99%
“…Konrad (1989) supported the validity of the GCCE under high initial pore water pressure through measurements of the pore water pressure during soil freezing tests with applied backpressure. Watanabe et al (2012) demonstrated the validity of the GCCE in the equilibrium state by measuring the pore water pressure using a micro-chilled-mirror hygrometer. The second type of supporting experiment involves indirect measurements of heaving pressure.…”
Section: Application Conditions Of the Gcce In Soil Freezingmentioning
confidence: 99%